The Effectiveness of Banana Flower in Reducing Emesis Gravidarum in First Trimester Of Pregnant Women - Nora Veri (Gaster, 2021)
Continuous emesis gravidarum will become hyperemesis gravidarum, which can increase the risk of pregnancy disorders. Pregnant women with hyperemesis gravidarum are at risk of experiencing dehydration, lack of carbohydrate and fat reserves in the body, small tears in the esophagus and stomach's mucous membrane. One of the diets in the case of emesis gravidarum is consuming foods high in carbohydrates. Banana flower is a food high in carbohydrates and vitamins, and antioxidants. Objectives; to determine the effectiveness of Banana flower in reducing emesis gravidarum in first-trimester pregnant women. Methods; quasi-experiment with pretest and post-test control group approaches. The sampling technique was simple random sampling. Banana flower with 200 g / day dose is given for seven days to pregnant women who experience emesis in the first trimester. The research group was divided into two: the banana flower treatment group and the control group, with 32 samples. Data analysis using the Shapiro-Wilk test and Wilcoxon test. Result; There was a significant difference in the intensity of emesis gravidarum between the group given banana flower and the control group with a p-value of 0.014. The banana flower can reduce the intensity of emesis gravidarum.